Liver gene regulation of hemostasis-related factors is altered by experimental snake envenomation in mice. - Ana Teresa Azevedo Sachetto; José Ricardo Jensen; Marcelo Larami Santoro (Public Library of Science (PLoS), 2020)
Few studies have addressed gene expression of hemostasis-related factors during acute thrombo-hemorrhagic diseases. Bites by the lanced-headed viper Bothrops jaracaca induce rapid hemostatic disturbances in victims, leading to systemic bleedings, thrombocytopenia and consumption coagulopathy. Although circulating levels of coagulation factors recover rapidly after administration of specific antivenom therapy, it is unclear if B. jararaca venom (BjV) upregulates the mRNA synthesis of hepatic hemostasis-related factors, or if the recovery occurs under basal conditions after the neutralization of venom components by antivenom. Thus, we aimed to investigate if BjV regulates gene expression of important hemostasis-related factors synthetized by the liver. On that account, Swiss mice were injected with saline or BjV (1.6 mg/kg b.w, s.c.), and after 3, 6 and 24 h blood samples and liver fragments were collected to analyze mRNA expression by real-time qPCR. Increased gene expression of fibrinogen chains, haptoglobin and STAT3 was observed during envenomation, particularly at 3 and 6 h. At 24h, mRNA levels of F10 were raised, while those of Serpinc1, Proc and Adamts13 were diminished. Surprisingly, F3 mRNA levels were steadily decreased at 3 h. Gene expression of Thpo, F7, F5 Tfpi, Mug1 was unaltered. mRNA levels of Vwf, P4hb, F8, F2, Plg, and Serpinf2 were minimally altered, but showed important associations with Nfkb1 gene expression. In conclusion, snakebite envenomation upregulates hepatic mRNA synthesis particularly of fibrinogen chains, and acute-phase markers. This response explains the fast recovery of fibrinogen levels after antivenom administration to patients bitten by B. jararaca snakes.